(untitled) (Agriculture, Food, and Natural Resources Journal, 2026)
This study assessed the effects of dietary supplementation of the combination of Garlic (Allium sativum) and Ginger (Zingiber officinale) powders on growth performance, nutrient utilization, and survival of Clarias gariepinus juveniles. Thus, 180 juveniles were randomly divided in triplicate into four treatments. In treatment-1, juveniles were fed with the control diet, while in treatments-2 and 3, they were fed a diet containing equal quantities of ginger and garlic to give the final proportions of 1% each; for treatment-4, a mixture of ginger and garlic was fed at 1%. Feeding trials were carried out for 56 days during which juveniles were fed twice daily at the rate of 5% of their body weight. Fish sampling was done every 14 days, during which juveniles per treatment were counted and measurements taken on a representative sample. The results obtained indicate that statistically the treatments are all the same. Treatment 3 recorded the lowest mean weight gain value of 4.27±1.00g, although this was statistically similar to the remaining treatments 1, 2, and 4 (p>0.05). A peak mean weight gain value of 7.03±1.67g was recorded in treatment 2, which was non-significantly different from other treatments. Treatment 3 also recorded the lowest percentage weight gain of 215.99±35.54, which was statistically non-significant (p>0.05). The highest value of 257.46±38.04 was observed in treatment-1. The feed conversion ratio values in all the treatments were statistically similar (p>0.05); however, the lowest value of 0.74±0.15 was recorded in treatment-2, and the highest value of 1.30±0.34 was recorded in treatment-3. Water parameters were registered at 2-week intervals; the results obtained are within the recommended range for aquaculture.